Benefits of adjuvant chemotherapy on pT1N0M0 triple-negative breast cancer survival outcomes: Beneficios de la quimioterapia adyuvante en los resultados de supervivencia del cáncer de mama triple negativo pT1N0M0 - Gomez, Henry L. (2024)
Introduction: Triple-negative breast cancer (TNBC) is notably an aggressive breast cancer (BC) subtype, leading to early relapse and poor prognosis. Effects of adjuvant chemotherapy among early-stage TNBC (pT1N0M0) patients remain unclear in different populations. Objectives: Our study aimed to determine the impact of adjuvant chemotherapy on overall survival (OS) and progression-free survival (PFS) within the specific subset of Peruvian pT1N0M0 TNBC patients (pT1a/b vs. pT1c). Methods: We retrospectively analyzed 2007 TNBC cases diagnosed between 2000-2014 at the Instituto Nacional de Enfermedades Neoplásicas (Lima, Peru). We included only non-metastatic TNBC cases and classified them as pT1N0M0 after surgery. TNBC patients who underwent neoadjuvant chemotherapy were excluded. We describe our population according to the tumor size from the residue disease (pT1a/b vs. pT1c). We used the Kaplan-Meier method test to determine differences in survival curves for OS and PFS. A Univariate Cox proportional hazards model was used to identify risk factors for PFS. Results: Our study cohort included 124 TNBC patients. Around 65.3% (n=81) were undergoing adjuvant chemotherapy. Notably, among pT1c patients, this treatment was more prevalent compared to pT1a/b (72.1% vs. 50.0%). Survival analysis showed no significant OS benefit from chemotherapy (HR:2.46,95%CI:0.74-8.13,p=0.13). However, a marked improvement in PFS was noted exclusively in the pT1c subgroup, with patients not treated with chemotherapy offering a prognostic risk (HR:20.10,95% CI:5.54-73.10,p<0.0001). pT1a/b patients demonstrated no benefit from chemotherapy regarding progression (HR:3.07,95% CI:0.27-34.50,p=0.34). Conclusion: Our study highlights that adjuvant chemotherapy significantly improves PFS in pT1cN0M0 TNBC patients but shows no clear benefit for smaller tumors (pT1a/bN0M0). Future research should focus on personalized chemotherapy strategies in early-stage TNBC to identify predictive markers for survival.